Penurunan Bakteri Coli pada Air Sungai Martapura Menggunakan Saringan Arang Sekam Padi - Syarifudin A. (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2017)
Abstract: The Decrease in the Number of Coli Bacteria in Water of Martapura River Using The Husk Charcoal Filter. The habits of the people along the Martapura river, defecates into the river, causing the river water polluted by Coli bacteria that be able to cause disease. Water treatment is required to improve the water quality of the Martapura river, one of them is using "the husk charcoal filter " to obtain clean water that meets health requirements. This study aimed to analyze the effectiveness of the husk charcoal filter, and determine the thickness of the filter were most effective to decrease the number of coli bacteria in water of Martapura river. In this design, was performed the initial measurements (pretest), performed the treatment and performed the second measurement (posttest), so it could be seen the effectiveness of the treatment. The "husk charcoal filter" was effective to Decrease the Number of Coli Bacteria in the water of Martapura river as much as 69,2% - 99,3%. However, a decrease in the number of coli bacteria still above the standards required by the Water Quality Standard class B, after filtration. Because it still found much bacteria after filtering, it is advisable to boil water to boiling before consumption, because heating is the most effective way to kill microbial pathogens that be able to cause disease. Keywords: Water of Martapura River; coli bacteria; the husk charcoal filter.